(+)-Catechin in a 1:2 Complex with Lysine Inhibits Cancer Cell Migration and Metastatic Take in Mice - Payen, Valéry L.; Porporato, Paolo E.; Danhier, Pierre; Vazeille, Thibaut; Blackman, Marine C. N. M.; May, Bronislav H.; Niebes, Paul; Sonveaux, Pierre (Frontiers in Pharmacology, 2017)
Metastasis is of dismal prognosis for cancer patients, but recent evidence in mouse models of cancer shows that metastasis prevention is a reachable clinical objective. These experiments indicate that altered mitochondrial activities are associated to the metastatic phenotype. Mitochondrial transfer from metastatic to non-metastatic cells can indeed transfer the metastatic phenotype, and metastatic progenitor cells differ from other cancer cells by a higher sublethal production of mitochondrial reactive oxygen species (ROS). Moreover, mitochondria-targeted antioxidants can prevent metastatic dissemination in mouse models of cancer. Comparatively, general antioxidants have unpredictable effects on cancer metastasis, most probably because they affect several cell types, several subcellular ROS production sites and, often, several endogenous oxidant species. Thus, targeting antioxidants to mitochondria could improve their antimetastatic activities, as previously exemplified with mitochondria-targeted mitoTEMPO and mitoQ that can prevent metastatic dissemination in cancer-bearing mice treated. Our objective in this study was to identify whether catechins, which are known to be potent antioxidants, can inhibit cancer cell migration in vitro and metastatic take in vivo. Comparative analysis of the response to epigallocatechin-3-gallate, (+)-catechin and (+)-catechin:lysine complexes revealed that, whereas all compounds had similar general antioxidant properties, (+)-catechin:lysine 1:2, but not the other tested catechins, can prevent metastatic take of melanoma cells to the lungs of mice. This compound possesses two net positive charges provided by lysines at physiological pH, which could provide high affinity for the negatively charged mitochondrial matrix. While this study reveals that (+)-catechin:lysine 1:2 has interesting antimetastatic effects, future experiments are needed to formally demonstrate the stability of the complex, its effective tropism for mitochondria and whether or not its activity can be globally attributed to its antioxidant activity at this precise subcellular location.